Friction material, brake pad and method of making same, braking system, vehicle
Patent Information
- Application Number
- CN202510578777.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
然而,目前刹车片产品在湿水工况下容易吸水,导致摩擦系数下降,影响制动效果
[0026]本申请的摩擦材料通过设置有机硅烷改性的硅溶胶,能够有效改善粘结剂的热稳定性,从而提高摩擦材料的热稳定性;且机硅烷改性的硅溶胶能使摩擦材料具有优异的疏水特性,进而能够有效防止水分子渗入含有摩擦材料的刹车片内部,从而保证刹车片在湿水工况下仍能保持良好的制动性能。
Smart Images

Figure BDA0005389817550000131 
Figure BDA0005389817550000132 
Figure BDA0005389817550000141
Abstract
Description
Technical Field
[0001] This application relates to the field of brake pads. Specifically, it relates to friction materials, brake pads and their manufacturing methods, braking systems, and vehicles. Background Technology
[0002] The braking process of a car mainly relies on the friction force of the friction material layer on the brake pads, converting kinetic energy into heat energy to decelerate or stop the vehicle. Brake pads need to possess characteristics such as high temperature resistance, wear resistance, and a stable coefficient of friction. However, current brake pad products are prone to absorbing water under wet conditions, leading to a decrease in the coefficient of friction and affecting braking performance. Summary of the Invention
[0003] This application aims to at least partially address one of the technical problems in the related art. Therefore, one objective of this application is to provide friction materials, brake pads, methods for manufacturing the same, braking systems, and vehicles. The brake pads of this application possess excellent thermal stability, strength, and hydrophobicity, enabling them to maintain good braking performance even under wet conditions.
[0004] A first aspect of this application is to provide a friction material comprising, based on the total weight of the friction material: 0.5-10 parts of organosilane-modified silica sol; 0.5-10 parts of binder; 40-80 parts of filler; and 20-40 parts of reinforcing fiber.
[0005] In some embodiments, the friction material comprises, based on its total weight: 2-8 parts of organosilane-modified silica sol; 2-8 parts of binder; 50-80 parts of filler; and 25-35 parts of reinforcing fiber.
[0006] In some embodiments, the mass ratio of the organosilane modified silica sol to the binder is (2-8):(6-4).
[0007] In some embodiments, the organosilane in the organosilane-modified silica sol includes at least one of chlorosilanes, methoxysilanes, ethoxysilanes, and epoxysilanes.
[0008] In some embodiments, the chlorosilanes include at least one of methyltrichlorosilane, dimethyldichlorosilane, phenyltrichlorosilane, and vinyltrichlorosilane;
[0009] The methoxysilanes include at least one of methyltrimethoxysilane, vinyltrimethoxysilane, and trifluoropropyltrimethoxysilane;
[0010] The ethoxysilanes include at least one of methyltriethoxysilane, tetraethyl orthosilicate, aminopropyltriethoxysilane, and perfluorooctyltriethoxysilane;
[0011] The epoxy silane includes epoxypropoxypropyltrimethylsilane.
[0012] In some embodiments, the silica sol in the organosilane-modified silica sol is a nanoscale silica sol.
[0013] In some embodiments, the adhesive comprises phenolic resin and / or polyimide resin.
[0014] In some embodiments, the filler includes at least one selected from copper powder, alumina, magnesium oxide, calcium oxide, titanium oxide, iron oxide, copper oxide, zinc oxide, barium oxide, strontium oxide, calcium carbonate, barium sulfate, mica, kaolin, wollastonite, molybdenum disulfide, graphite, and carbon black.
[0015] In some embodiments, the reinforcing fiber includes at least one selected from copper fiber, steel fiber, alumina ceramic fiber, zirconia ceramic fiber, aramid fiber, basalt fiber, carbon fiber, polypropylene fiber, and polyethylene fiber.
[0016] In some embodiments, 1-10 parts of an auxiliary agent are included; and / or, the auxiliary agent includes at least one of a curing agent, a plasticizer, a coupling agent, a flame retardant, and an antioxidant.
[0017] A second aspect of this application is to provide a brake pad including a friction layer comprising the aforementioned friction material.
[0018] In some embodiments, the water contact angle of the brake pads ranges from 130° to 170°.
[0019] A third aspect of this application is to provide a method for preparing a brake pad, comprising preparing the aforementioned friction material into a friction layer and then fabricating the friction layer into a brake pad.
[0020] In some embodiments, the method for preparing the brake pads includes the following steps:
[0021] S1. The organosilane-modified silica sol, the filler, and the first solvent are mixed and then dried to obtain a first mixture;
[0022] S2. The first mixture, the binder, and the second solvent are mixed and then dried to obtain the second mixture;
[0023] S3. Mix the second mixture and the reinforcing fiber; then hot press to form the brake pad.
[0024] A fourth aspect of this application is to provide a braking system comprising the aforementioned friction material, or the aforementioned brake pad, or a brake pad manufactured by the aforementioned brake pad manufacturing method.
[0025] The fifth aspect of this application is to provide a vehicle comprising the aforementioned friction material, or the aforementioned brake pad, or a brake pad manufactured by the aforementioned brake pad manufacturing method, or the aforementioned braking system.
[0026] The friction material of this application, by setting an organosilane-modified silica sol, can effectively improve the thermal stability of the binder, thereby improving the thermal stability of the friction material; and the organosilane-modified silica sol can give the friction material excellent hydrophobic properties, thereby effectively preventing water molecules from penetrating into the brake pad containing the friction material, thus ensuring that the brake pad can still maintain good braking performance under wet conditions. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0028] This application provides a friction material comprising, based on the total weight of the friction material: 0.5-10 parts of organosilane-modified silica sol; 0.5-10 parts of binder; 40-80 parts of filler; and 20-40 parts of reinforcing fiber.
[0029] The friction material of this application uses a specific ratio of organosilane-modified silica sol, which can effectively improve the thermal stability of the binder. The interaction of various substances enhances the thermal stability of the friction material. Furthermore, the organosilane-modified silica sol gives the friction material excellent hydrophobic properties, which can effectively prevent water molecules from penetrating into the brake pad containing the friction material. This ensures that the brake pad maintains good braking performance under wet conditions, and the friction material exhibits high frictional stability under high temperature and wet environments.
[0030] The silica sol in this application is modified with organosilanes. Organosilanes (RnSiX(4-n)) are a class of organosilicon compounds composed of organic groups R (alkyl, aryl, alkenyl, etc.) and hydrolytic groups X (amino, hydroxyl, methoxy, ethoxy, etc.). Using organosilane-modified silica sol introduces more groups that can participate in hydrolysis and condensation, increasing the crosslinking density of the silica sol and further improving the bonding strength between materials. If silica sol is used alone, it is mainly composed of inorganic silica, and the proportion of Si-O-Si bonds formed after curing is slightly low, insufficient to form a dense crosslinked network, resulting in poor adhesion. Furthermore, the Si-O bonds are rigid and lack deformation capacity, making the surface of the cured material prone to defects such as cracks and micropores.
[0031] In some embodiments, the organosilane in the organosilane-modified silica sol includes at least one of chlorosilanes, methoxysilanes, ethoxysilanes, and epoxysilanes. The chlorosilanes include at least one of methyltrichlorosilane, dimethyldichlorosilane, phenyltrichlorosilane, and vinyltrichlorosilane; the methoxysilanes include at least one of methyltrimethoxysilane, vinyltrimethoxysilane, and trifluoropropyltrimethoxysilane; the ethoxysilanes include at least one of methyltriethoxysilane, tetraethyl orthosilicate, aminopropyltriethoxysilane, and perfluorooctyltriethoxysilane; and the epoxysilanes include glycidoxypropyltrimethylsilane.
[0032] In some embodiments, the silica sol in the organosilane-modified silica sol is a nanoscale silica sol, for example, it can be 1-100 nm, which can enhance the thermal stability of the friction material in one step.
[0033] In some embodiments, the organosilane-modified silica sol can be, for example, 0.5 parts, 1 part, 2 parts, 3 parts, 5 parts, 8 parts, or 10 parts, preferably 2-8 parts, and more preferably 3-6 parts. The binder can be, for example, 0.5 parts, 1 part, 2 parts, 3 parts, 5 parts, 8 parts, or 10 parts, preferably 2-8 parts, and more preferably 3-6 parts.
[0034] In some embodiments, the binder includes phenolic resin and / or polyimide resin. These resins are prone to thermal decomposition at high temperatures, primarily due to the breakage of CO bonds (bond energy approximately 360 kJ / mol) and C / C bonds in their molecular structure, leading to a decline in material properties. After curing, organosilane-modified silica sol forms high-temperature resistant Si-O-Si bonds (bond energy approximately 460 kJ / mol), which can form a Si-OCOR structure with the resin, further enhancing interfacial compatibility with phenolic resin and / or polyimide resin. The cured organosilane-modified silica sol possesses a relatively rigid three-dimensional network structure, effectively dispersing thermal stress at high temperatures and delaying the thermal decomposition of phenolic resin and / or polyimide resin.
[0035] In some embodiments, the thermal stability of the binder can be further enhanced by controlling the mass ratio of organosilane-modified silica sol to binder to be (2-8):(6-4).
[0036] In some embodiments, the filler includes at least one selected from copper powder, alumina, magnesium oxide, calcium oxide, titanium oxide, iron oxide, copper oxide, zinc oxide, barium oxide, strontium oxide, calcium carbonate, barium sulfate, mica, kaolin, wollastonite, molybdenum disulfide, graphite, and carbon black. Adding these substances to the friction material can improve its frictional properties. Specifically, copper powder and carbon black act as thermal conductors, helping to quickly disperse the heat generated by friction and prevent localized overheating. Alumina and wollastonite can increase the coefficient of friction and wear resistance. Magnesium oxide and calcium oxide provide an alkaline environment to slow down the corrosion of metals in brake pads. Titanium oxide, zinc oxide, barium oxide, strontium oxide, and barium sulfate can act as friction stabilizers at high temperatures. Iron oxide, copper oxide, kaolin, and calcium carbonate are inexpensive fillers that can be combined in different proportions to adjust the frictional properties of brake pads. Mica and carbon black improve brake noise. Molybdenum disulfide, as a high-temperature lubricant, and graphite, as a low-temperature lubricant, can reduce brake pad wear. The filler can be, for example, 40 parts, 45 parts, 50 parts, 60 parts, 70 parts, or 80 parts, preferably 50-80 parts.
[0037] In some embodiments, the filler includes a combination of alumina, wollastonite, barium sulfate, copper powder, calcium oxide, mica, molybdenum disulfide, and graphite. For example, it may be 16-20 parts alumina, 8-12 parts wollastonite, 4-8 parts barium sulfate, 6-10 parts copper powder, 3-7 parts calcium oxide, 1-3 parts mica, 3-7 parts molybdenum disulfide, and 6-10 parts graphite, to further improve the friction properties of the friction material.
[0038] In some embodiments, the reinforcing fibers include at least one of metal fibers (copper fibers, steel fibers), ceramic fibers (alumina ceramic fibers, zirconia ceramic fibers), aramid fibers, basalt fibers, carbon fibers, polypropylene fibers, and polyethylene fibers. The three-dimensional network structure formed by the reinforcing fibers prevents the material from delaminating and fragmenting upon impact. Specifically, aramid fibers, for example, with high modulus, provide the brake pads with a certain elastic modulus, making the deformation of the brake pads controllable and ensuring stable contact between the brake pads and the disc; carbon fibers have good heat resistance, and metal fibers have good thermal conductivity, improving heat resistance; ceramic fibers have high hardness and wear resistance, adjusting friction performance. The reinforcing fibers can be, for example, 20 parts, 25 parts, 30 parts, 35 parts, or 40 parts, preferably 25-35 parts.
[0039] In some embodiments, the reinforcing fibers include metal fibers (specifically copper fibers and / or steel fibers) and aramid fibers, for example, 24-28 parts of metal fibers and 1-3 parts of aramid fibers. This further improves the tribological and mechanical properties of the friction material.
[0040] In some embodiments, the friction material further includes 1-10 parts of an auxiliary agent. For example, the auxiliary agent includes at least one selected from a curing agent, plasticizer, coupling agent, flame retardant, and antioxidant to further improve the frictional properties, thermal stability, and oxidation resistance of the friction material. Specifically, the curing agent may include at least one selected from hexamethylene, paraformaldehyde, and maleic anhydride; the plasticizer may include at least one selected from tricresyl phosphate and phthalate; and the coupling agent may include at least one selected from γ-aminopropyltriethoxysilane (KH-550) and γ-glycidoxypropyltrimethoxysilane (KH-560). The auxiliary agent may be, for example, 1 part, 2 parts, 3 parts, 5 parts, 8 parts, or 10 parts, preferably 0.1-2 parts.
[0041] In some embodiments, coupling agents are used to modify the surface of the filler in the friction material to enhance its interfacial bonding with the matrix material, thereby improving the overall stability of the friction material.
[0042] This application also provides a brake pad, including a friction layer comprising the aforementioned friction material. This brake pad exhibits excellent thermal stability and frictional properties, and maintains good braking performance even under wet conditions.
[0043] In some implementations, the water contact angle of the brake pad surface ranges from 130° to 170°, enabling the brake pads to maintain good braking performance even in wet conditions.
[0044] This application also provides a method for preparing a brake pad, wherein the aforementioned friction material is prepared into a friction layer; and the friction layer is fabricated into a brake pad.
[0045] In some embodiments, the method for preparing the brake pads includes the following steps:
[0046] S1. The organosilane-modified silica sol, the filler, and the first solvent are mixed and then dried to obtain a first mixture;
[0047] S2. The first mixture, the binder, and the second solvent are mixed and then dried to obtain the second mixture;
[0048] S3. Mix the second mixture and the reinforcing fiber; then hot press to form the brake pad.
[0049] In some embodiments, step S1 specifically includes: mixing 0.5-10 parts of organosilane modified silica sol, 40-80 parts of filler and 1-10 parts of auxiliary agent with a first solvent, such as 10-30 parts of alcohol solution, in a mixer for 60-120 minutes; placing the uniformly mixed material in an oven at 60℃-100℃ and drying it to constant weight to obtain the first mixture.
[0050] In some embodiments, step S2 specifically includes: mixing the first mixture with 0.5-10 parts of binder (e.g., phenolic resin and / or polyimide resin) and a second solvent (e.g., 10-30 parts of alcohol solution) in a mixer for 60-120 minutes, and drying the uniformly mixed material in an oven at 60°C-100°C until constant weight to obtain the second mixture.
[0051] In some embodiments, step S2 specifically includes: mixing the second mixture and 20-40 parts of reinforcing fiber evenly, and then hot pressing them, wherein the temperature is 150℃-300℃, the pressure is 30MPa-50MPa, and the holding time is 10-30min, to obtain a brake pad.
[0052] In some embodiments, step S2 specifically includes: mixing the second mixture with 20-40 parts of reinforcing fiber and 5-10 parts of graphite until uniform, and then hot-pressing it.
[0053] In some implementations, the brake pads can be chamfered or otherwise processed according to the actual situation to obtain finished brake pads.
[0054] A fourth aspect of this application is to provide a braking system comprising the aforementioned friction material, or the aforementioned brake pad, or a brake pad manufactured by the aforementioned brake pad manufacturing method.
[0055] The fifth aspect of this application is to provide a vehicle comprising the aforementioned friction material, or the aforementioned brake pad, or a brake pad manufactured by the aforementioned brake pad manufacturing method, or the aforementioned braking system.
[0056] The present application will be described in detail below through embodiments, but the present application is not limited to the following embodiments.
[0057] Example 1
[0058] (1) Mix 1 part by weight of organosilane modified silica sol (specifically γ-aminopropyltriethoxysilane (KH-550) modified silica sol), 18 parts by weight of alumina, 10 parts by weight of wollastonite, 6 parts by weight of barium sulfate, 8 parts by weight of copper powder, 5 parts by weight of calcium oxide, 2 parts by weight of mica, 5 parts by weight of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min. Then place the uniformly mixed material in an oven at 60°C and dry it to constant weight.
[0059] (2) Mix the material obtained by wet mixing in step 1 with 9 parts by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. Place the uniformly mixed material in an oven at 60°C and dry it to constant weight.
[0060] (3) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0061] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0062] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0063] Example 2
[0064] (1) Mix 2 parts by weight of organosilane modified silica sol, 18 parts of alumina, 10 parts of wollastonite, 6 parts of barium sulfate, 8 parts of copper powder, 5 parts of calcium oxide, 2 parts of mica, 5 parts of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min, and then place the uniformly mixed material in an oven at 60°C to dry to constant weight.
[0065] (2) The material obtained by wet mixing in step 1 is mixed again with 8 parts by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. The uniformly mixed material is placed in an oven at 60°C and dried to constant weight.
[0066] (3) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0067] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0068] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0069] Example 3
[0070] (1) Mix 4 parts by weight of organosilane modified silica sol, 18 parts of alumina, 10 parts of wollastonite, 6 parts of barium sulfate, 8 parts of copper powder, 5 parts of calcium oxide, 2 parts of mica, 5 parts of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min, and then place the uniformly mixed material in an oven at 60°C to dry to constant weight.
[0071] (2) The material obtained by wet mixing in step 1 is mixed again with 6 parts by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. The uniformly mixed material is placed in an oven at 60°C and dried to constant weight.
[0072] (3) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0073] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0074] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0075] Example 4
[0076] (1) Mix 5 parts by weight of organosilane modified silica sol, 18 parts of alumina, 10 parts of wollastonite, 6 parts of barium sulfate, 8 parts of copper powder, 5 parts of calcium oxide, 2 parts of mica, 5 parts of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min, and then place the uniformly mixed material in an oven at 60°C to dry to constant weight.
[0077] (2) The material obtained by wet mixing in step 1 is mixed again with 5 parts by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. The mixed material is then placed in an oven at 60°C and dried to constant weight.
[0078] (3) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0079] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0080] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0081] Example 5
[0082] (1) Mix 8 parts by weight of organosilane modified silica sol, 18 parts of alumina, 10 parts of wollastonite, 6 parts of barium sulfate, 8 parts of copper powder, 5 parts of calcium oxide, 2 parts of mica, 5 parts of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min, and then place the uniformly mixed material in an oven at 60°C to dry to constant weight.
[0083] (2) The material obtained by wet mixing in step 1 is mixed again with 2 parts by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. The uniformly mixed material is placed in an oven at 60°C and dried to constant weight.
[0084] (3) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0085] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0086] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0087] Example 6
[0088] (1) Mix 9 parts by weight of organosilane modified silica sol, 18 parts of alumina, 10 parts of wollastonite, 6 parts of barium sulfate, 8 parts of copper powder, 5 parts of calcium oxide, 2 parts of mica, 5 parts of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min, and then dry the uniformly mixed material in an oven at 60°C until constant weight.
[0089] (2) The material obtained by wet mixing in step 1 is mixed again with 1 part by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. The mixed material is then placed in an oven at 60°C and dried to constant weight.
[0090] (3) Mix the material obtained by wet mixing in step 2, 3 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0091] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0092] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0093] Comparative Example 1
[0094] (1) Mix 10 parts by weight of phenolic resin, 30 parts by weight of silica, 8 parts by weight of kaolin, 10 parts by weight of graphite, 10 parts by weight of barium sulfate, 2 parts by weight of silane coupling agent and 30 parts by weight of alcohol solution in a mixer for 100 min, and then place the uniformly mixed material in an oven at 60°C to dry to constant weight.
[0095] (2) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0096] (3) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0097] (4) The hot-pressed brake pads are processed by chamfering and other processes to obtain finished brake pads.
[0098] Comparative Example 2
[0099] (1) Mix 10 parts by weight of organosilane modified silica sol, 30 parts by weight of silica, 8 parts by weight of kaolin, 10 parts by weight of graphite, 10 parts by weight of barium sulfate, 2 parts by weight of silane coupling agent and 30 parts by weight of alcohol solution in a mixer for 100 min, and then place the uniformly mixed material in an oven at 60°C to dry to constant weight.
[0100] (2) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0101] (3) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0102] (4) The hot-pressed brake pads are processed by chamfering and other processes to obtain finished brake pads.
[0103] Comparative Example 3
[0104] (1) Mix 2 parts by weight of unmodified silica sol, 18 parts of alumina, 10 parts of wollastonite, 6 parts of barium sulfate, 8 parts of copper powder, 5 parts of calcium oxide, 2 parts of mica, 5 parts of molybdenum disulfide and 30 parts by weight of alcohol solution in a mixer for 100 min, and then dry the uniformly mixed material in an oven at 60°C until constant weight.
[0105] (2) The material obtained by wet mixing in step 1 is mixed again with 8 parts by weight of phenolic resin and 30 parts by weight of alcohol solution in a mixer for 100 minutes. The uniformly mixed material is placed in an oven at 60°C and dried to constant weight.
[0106] (3) Mix the material obtained by wet mixing in step 2, 2 parts by weight of aramid fiber, 26 parts by weight of steel fiber and 8 parts by weight of graphite evenly in a high-speed mixer.
[0107] (4) Pour the well-mixed material into the mold and hot press it at 220°C with a pressure of 50MPa and a holding time of 20min.
[0108] (5) The hot-pressed brake pads are chamfered and processed to obtain finished brake pads.
[0109] Performance testing
[0110] Porosity and density testing: vacuum saturated solution method.
[0111] Shear strength test: GB 5763-2018.
[0112] Compression strain test: ISO 26865.
[0113] Water contact angle test: The water contact angle was tested using a contact angle measuring instrument (DYT-600Z).
[0114] Friction coefficient and wear amount test: The test was conducted on a friction testing machine (SAE J2522).
[0115] TG-DSC test: Mettler TGA / DSC3+ model tester, 30℃ to 700℃, heating rate 10℃ / min.
[0116] Table 1
[0117]
[0118] Table 2
[0119]
[0120]
[0121] As can be seen from the results in Tables 1 and 2, compared with the comparative example, the brake pads prepared in this application have high frictional stability under high temperature and wet conditions.
[0122] The preferred embodiments of this application have been described in detail above. However, this application is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this application, various simple modifications can be made to the technical solution of this application, and these simple modifications all fall within the protection scope of this application.
[0123] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not describe the various possible combinations separately.
[0124] Furthermore, various different implementations of this application can be combined in any way, as long as they do not violate the spirit of this application, they should also be regarded as the content disclosed in this application.
Claims
1. A friction material, characterized in that, Based on the total weight of the friction material, it comprises: 0.5-10 parts of organosilane-modified silica sol; 0.5-10 parts of binder; 40-80 parts of filler; and 20-40 parts of reinforcing fiber.
2. The friction material according to claim 1, characterized in that, Based on the total weight of the friction material, it comprises: 2-8 parts of organosilane-modified silica sol; 2-8 parts of binder; 50-80 parts of filler; and 25-35 parts of reinforcing fiber.
3. The friction material according to claim 1, characterized in that, The mass ratio of the organosilane-modified silica sol to the binder is (2-8):(6-4).
4. The friction material according to claim 1, characterized in that, The organosilane in the organosilane-modified silica sol includes at least one of chlorosilanes, methoxysilanes, ethoxysilanes, and epoxysilanes.
5. The friction material according to claim 4, characterized in that, The chlorosilanes include at least one of methyltrichlorosilane, dimethyldichlorosilane, phenyltrichlorosilane, and vinyltrichlorosilane; the methoxysilanes include at least one of methyltrimethoxysilane, vinyltrimethoxysilane, and trifluoropropyltrimethoxysilane. The ethoxysilanes include at least one of methyltriethoxysilane, tetraethyl orthosilicate, aminopropyltriethoxysilane, and perfluorooctyltriethoxysilane; The epoxy silane includes epoxypropoxypropyltrimethylsilane.
6. The friction material according to claim 1, characterized in that, The silica sol in the organosilane modified silica sol is a nanoscale silica sol.
7. The friction material according to claim 1, characterized in that, The adhesive includes phenolic resin and / or polyimide resin.
8. The friction material according to claim 1, characterized in that, The filler includes at least one of copper powder, alumina, magnesium oxide, calcium oxide, titanium oxide, iron oxide, copper oxide, zinc oxide, barium oxide, strontium oxide, calcium carbonate, barium sulfate, mica, kaolin, wollastonite, molybdenum disulfide, graphite, and carbon black.
9. The friction material according to claim 1, characterized in that, The reinforcing fibers include at least one of copper fibers, steel fibers, alumina ceramic fibers, zirconia ceramic fibers, aramid fibers, basalt fibers, carbon fibers, polypropylene fibers, and polyethylene fibers.
10. The friction material according to any one of claims 1-9, characterized in that, It includes 1-10 parts of an auxiliary agent; and / or, the auxiliary agent includes at least one of a curing agent, a plasticizer, a coupling agent, a flame retardant, and an antioxidant.
11. A brake pad, characterized in that, It includes a friction layer, which comprises the friction material according to any one of claims 1-9.
12. The brake pad according to claim 11, characterized in that, The water contact angle of the brake pads ranges from 130° to 170°.
13. A method for preparing brake pads, characterized in that, The friction material according to any one of claims 1-10 is prepared into a friction layer; the friction layer is made into a brake pad.
14. The method for preparing brake pads according to claim 13, characterized in that, Includes the following steps: S1. The organosilane-modified silica sol, the filler, and the first solvent are mixed and then dried to obtain a first mixture; S2. The first mixture, the binder, and the second solvent are mixed and then dried to obtain the second mixture; S3. Mix the second mixture and the reinforcing fiber; then hot press to form the brake pad.
15. A braking system, characterized in that, The brake pads include the friction material according to any one of claims 1-10, the brake pads according to any one of claims 11-12, or the brake pads prepared by the method according to any one of claims 13-14.
16. A vehicle, characterized in that, This includes the friction material according to any one of claims 1-10, or the brake pad according to any one of claims 11-12, or the brake pad prepared by the method according to any one of claims 13-14, or the braking system according to claim 15.